Sturgeon Aquaculture - Specialized Techniques Determining the Stage of Sexual Maturity in Female Sturgeon for Artificial Spawning The Egg Polarization Index or PI - Frank A. Chapman; Joel P. Van Eenennaam (EDIS)
FA-153, a 5-page illustrated fact sheet by Frank A. Chapman and Joel P. Van Eenennaam, describes a simple field and laboratory test used to assist in predicting ovulatory response in female sturgeon, which uses the egg size and position of the nucleus in the cytoplasm as indicators — the principle behind it, materials needed, biopsy procedure, and how to determine the egg polarization index. Published by the UF Department of Fisheries and Aquatic Sciences, December 2007.